Recognising the risks: perceptions of higher education amongst young white British males from areas of educational disadvantages. Issue 4 (2nd October 2022) - Raven, Neil
ABSTRACT: Comparatively few young white males from poorer backgrounds progress to university. This paper considers evidence gathered from a study that explores the educational ambitions of these young men from five areas of educational disadvantage in North West England, at two stages in their learner journeys. The first stage relates to school year 10 (14–15 year olds), as pupils work towards their level 2 qualifications. The second focuses on year 12 (16–17 year olds), as post-16 options are embarked upon and attention is turned to longer-term plans. What emerges from this study are a number of shared concerns over higher education as a destination. In supporting claims made in various other studies that have considered learners from widening participation backgrounds more generally, it is argued that these can be expressed in terms of costs. For this group, the potential benefits of HE must be weighed against a range of consequences that, in scale and extent, are unlikely to be encountered by their more affluent peers, and that may not be so acutely felt by those from some other under-represented populations. The study concludes by arguing that practitioners should acknowledge these consequences when developing outreach interventions for this group.